Protective Effect of Mesenchymal Stem Cell-Derived Extracellular Vesicles on Inner Ear Sensorineural Cells Affected by Cisplatin - Maria Perde-Schrepler; Ioana Brie; Mihai Cenariu; Sergiu Chira; Lajos Raduly; Liviuta Budisan; Ioana Berindan-Neagoe; Rares Stiufiuc; Maximilian Dindelegan; Cristina Blebea; Emoke Pall; Alma Aurelia Maniu (Medicina, 2025)
Background and Objectives: Extracellular vesicles (EVs) derived from mesenchymal stem cells have gained much attention as potential therapeutic agents in many diseases, including hearing disorders such as sensorineural hearing loss (SNHL). EVs inherit similar therapeutic effects, including the stimulation of tissue regeneration from the parental cells. The aim of our study was to isolate EVs produced by MSCs and use them to treat inner ear cells in culture to evaluate their protective potential against the damaging effect of an ototoxic drug. Materials and Methods: We isolated MSC-derived EVs by precipitation and characterized them by number, size, and morphology using nanoparticle tracking analysis and TEM, evaluated the protein concentration by BCA assay and the presence of EV markers CD9, CD63, and CD81 by the Dot Blot immunoblotting method. HEI-OC1 inner ear cell line was treated with EVs either alone or followed by Cisplatin. We assessed the uptake of EVs in HEI-OC1 cells by fluorescence microscopy after PKH26 labeling, ROS production by the DCFDA (dichlorfluorescein diacetate) assay, cellular viability by Alamar Blue assay, and apoptosis with the Annexin V/Propidium Iodide method. Results: The isolated EVs had mean dimensions of 184.4 nms and the concentration of the EV suspension was 180 × 106 particles/mL. TEM analysis showed intact vesicular structures with lipid-bilayer membranes having similar sizes with those measured by NTA. The PKH26-labeled EVs were observed in the HEI-OC1 cells after 24 h incubation, the amount increasing with the concentration. EVs reduced ROS production and increased the number of viable cells both alone and as pretreatment before Cisplatin, dose-dependently. Cells in early apoptosis were inhibited by EVs, while those in late apoptosis were enhanced, both with and without Cisplatin. Conclusions: EVs secreted by MSC protected HEI-OC1 cells against Cisplatin toxicity, reduced ROS production, and stimulated cell viability and the elimination of damaged cells by apoptosis, protecting the HEI-OC1 cells against Cisplatin-induced damage.